Pengembangan Media Pembelajaran Infografis Berbasis Canva Melalui Konten Tiktok Pada Pelajaran Informatika di SMK Negeri 1 Suwawa - Masi, Muhammad Ali; Mulyanto, Arip; Mas’ud, Huzaima; Rohandi, Manda; Kadim, Ahmad Azhar; Muthia, Muthia (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2024)
The use of technology in education continues to increase, including the utilization of the TikTok application as a medium for developing Canva-based infographics as a learning tool. This study is motivated by the lack of visual elements in the learning process, which impacts the low attractiveness of the material for students. Students often receive material only verbally without adequate visual support, making the material less engaging and ultimately reducing students' interest and motivation in learning. This research aims to develop infographic-based learning media using Canva, displayed through TikTok content, designed to address student boredom and the lack of appealing visualization in material delivery. Infographics, which combine visual elements and information, are designed to simplify the understanding of material, while TikTok is chosen for its ability to dynamically present content through slideshow and hashtag features. The development method used is the 4D method, which includes four stages: Define, Design, Develop, and Disseminate. Validation results from subject matter experts indicate that this media has a feasibility percentage of 96%, categorized as very feasible. Validation from media experts also obtained an average feasibility score of 93.64%, showing that the media meets quality standards in design and presentation, also categorized as very feasible. Furthermore, assessments from 26 student respondents reveal that this media is attractive and effective, with a score of 94%, also categorized as very feasible. Based on these results, Canva-based infographic learning media through TikTok content is highly feasible and attractive for application in the learning process.Kata kunci: Infografis, Media Pembelajara, Metode 4D, Pengembangan Media, Tiktok